LANGUAGE LITERACY AND MATHEMATICS COMPETENCE EFFECT TOWARD WORD PROBLEMS SOLVING - Namirah Fatmanissa; Rahmat Sagara (Jurnal Infinity, 2017)
This study aims to know the effect of language literacy and basic Mathematics competence toward students’ ability to solve word problems. The research was done by giving three sets of questions; language literacy (LL) set, basic Mathematics competence (BM) set, and word problems (WP) set; to the research sample.  Research sample was 315 tenth grade students from five schools in Jakarta. Score of students in each set was analyzed as research data. Score of LL set was treated as data of independent variable 1, score of BM set was treated as data of independent variable 2, and score of WP set as data of dependent variable. Preliminary data analyses, such as normality, validity, and reliability test, were done. Then, data was analyzed using Wilcoxon test and calculation of R-square. The result shows that each of independent variable affects dependent variable with BM variable has more effect on WP variable.